(In)movilidades en torno al espacio carcelario: relaciones de género y gobernabilidad en cárceles federales en Buenos Aires, Argentina - Pereyra Iraola, Victoria (2017)
(Im)mobility studies have tended to associate mobility with characteristics coded as masculine and immobility with characteristics coded as feminine. In the specific case of male prison contexts, however, these dichotomous categories seem to blur. Based on a study carried out with women that visit their male relatives in federal prisons in Buenos Aires, this article explores the link between mobility and gender relations in prison contexts. Through the analysis of the weekly trips made by these women to prisons, the article analyses the modes of production and regulation of (im)mobility that are built around the movement of bodies and goods in prison units and their effects in transforming the extent of prison walls, the daily lives of these families and the uses of urban space.